Association between urinary thiodiglycolic acid level and hepatic function or fibrosis index in school-aged children living near a petrochemical complex. (January 2019) - Wang, Chih-Wen; Liao, Kai-Wei; Chan, Chang-Chuan; Yu, Ming-Lung; Chuang, Hung-Yi; Chiang, Hung-Che; Huang, Po-Chin
Abstract: The effect of exposure to vinyl chloride monomer (VCM) on susceptibility to hepatotoxicity in children is unknown, although experimental studies have demonstrated a significantly increased risk of hepatocellular carcinoma in rodents exposed to VCM in early life. Epidemiological studies have revealed a high prevalence of liver fibrosis and abnormal liver function in workers exposed to high VCM levels. We aimed to assess the association among urinary thiodiglycolic acid (TDGA) level, abnormal liver function, and hepatic fibrosis in school-aged children living near a petrochemical complex. A total of 303 school-aged (6–13 years) children within 10 km nearly a petrochemical complex was recruited in central Taiwan. First-morning urine and blood samples were collected from each subject, and urinary TDGA level was analyzed through liquid chromatography–tandem mass spectrometry. Liver function was determined by serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels. Hepatic fibrosis was assessed using the AST to platelet ratio index (APRI) and fibrosis-4 score (FIB-4). Risk of hepatotoxicity induced by TDGA exposure was estimated using multivariate logistic regression. The median (range, subclinically abnormal %) AST and ALT levels of all subjects were 26.0 (17.0–99.0, 25.7%) and 15.0 (7.0–211.0, 5.9%) IU/L, respectively. Children in the highest urinary TDGA quartile (≥160.0 μg/g creatinine) exhibited significantly elevated median AST levels compared with those in the lowest quartiles (<35.4 μg/g creatinine, p = 0.033). After adjustment for potential confounding factors, children in the highest quartiles (Q4 ) of TDGA level had significantly increased odds ratio (OR) of subclinically abnormal AST (OR = 3.86; 95% confidence interval: 1.54–9.67) compared with those in the lowest quartile. A dose-response trend (p = 0.004) was observed. Our findings support the hypothesis that elevated urinary TDGA level in children living near petrochemical complex is associated with susceptibility to hepatotoxicity. Graphical abstract: Image 1 Highlights: We used urinary thiodiglycolic acid (TDGA) as biomarker of vinyl chloride monomer (VCM) exposure. Children had significantly elevated AST level in the highest urinary TDGA quartile. Urinary TDGA exhibited increased risk of subclinically abnormal AST and liver fibrosis in children. Subclinically abnormal AST is a health index in children exposed to VCM. Abstract : Urinary thiodiglycolic acid level is associated with hepatotoxicity in school-aged children living near a petrochemical complex.